Caracterização das alterações teciduais em dois modelos de indução de doença periodontal experimental em camundongos - Mascarenhas, Vinicius Ibiapina [UNESP] (2014)
Periodontitis is an infectious disease characterized by a chronic inflammatory process of periodontal mediated and modulated by the host. This disease results in the destruction of conective tissue and supporting tissues of the teeth. In order to evaluate both the pathogenesis of periodontal disease and the various treatment modalities, different animal models of experimental periodontitis have been proposed and used. The benefit of using these models results in the fact that they allow an evaluation of a longitudinal disease with similar characteristics of start and progression in several animals. The aim of this study was to characterize and evaluate tissue changes caused by two models of experimental periodontal disease in mice: ligature and oral gavage. For this, 48 C57/BL6 mice wild type (WT) mice were divided into 4 groups: Group C - Negative Control, Group L - Ligature (induction of periodontal disease by ligatures), Group G-Pg - Porphyromonas gingivalis Gavage (induction by Pg inoculations) and Group G-PgFn - Porphyromonas gingivalis + Fusobacterium nucleatum Gavage. The animals were sacrificed at two experimental periods: 45 and 60 days after the induction onset of periodontal disease. Significant bone loss only in the group L by means of stereometric analysis, computed microtomography (μCT) and immunohistochemistry was observed. The bacterial colonization in groups of gavage was confirmed by PCR in real time. We conclude that the model of ligature was effective in inducing periodontal disease parameters used in contrast to oral gavage.